Miłosierdzie i gospodarka – od gór pobożnych do wspólnego ratowania się w nieszczęściu - Duda, Józef (Annales. Etyka w Życiu Gospodarczym, 2013)
Charity, the core of the Gospel ethos, became one of the founding ideas of European civilization and distinguished it from others. In Polish territories, as in other Western European countries, charity work was conducted primarily by the Church, which together with its sense of Gospel duty, defended the weak by concerning itself with economic development. For this purpose, charitable credit institutions, so-called mounts of piety (montes pietatis), were established. They were continued by reformers, in a somewhat changed form, until the decline of the Polish Commonwealth (Republic). The most original institution of this kind was Rev. Stanisław Staszic’s foundation: the Hrubieszów Agricultural Society, which survived until the days of the Polish People’s Republic.